Choir room - Ghosh, Ayan (2023)
Entry to the St. Thomas Church is from the west (seen on the right). Walls on both sides of the entrance lobby are covered in memorials. The antechamber (seen in the center) is used as the choir room. Above the choir room door hangs an old photograph of the Church Gate, which was demolished along with the ramparts of Bombay Fort in the mid-1860s.